2017
DOI: 10.1186/s12966-017-0474-2
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects of a web-based cancer aftercare intervention on moderate physical activity and vegetable consumption among early cancer survivors: a randomized controlled trial

Abstract: BackgroundThe number of cancer survivors is growing. Negative physical and psychosocial consequences of cancer treatment can occur during survivorship. Following healthy lifestyle recommendations is beneficial to increase quality of life and to reduce the risk of cancer recurrence and comorbidities. To meet individual needs, web-based interventions can supply a large population of cancer survivors with easily accessible and personalized information. Evidence concerning the long-term effects of web-based cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
130
3
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(136 citation statements)
references
References 72 publications
2
130
3
1
Order By: Relevance
“…Additionally, similar results were not observed in our intent-to-treat analysis. To our knowledge, only three Web-based intervention studies among cancer survivors have intervened on dietary intake [24,29,32], with two showing improvements [29,33]. It could be that 3-months was not sufficient to produce changes in dietary intake in our sample.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Additionally, similar results were not observed in our intent-to-treat analysis. To our knowledge, only three Web-based intervention studies among cancer survivors have intervened on dietary intake [24,29,32], with two showing improvements [29,33]. It could be that 3-months was not sufficient to produce changes in dietary intake in our sample.…”
Section: Discussionmentioning
confidence: 82%
“…It could be that 3-months was not sufficient to produce changes in dietary intake in our sample. Recently Kanera et al [33] demonstrated an improvement in dietary intake at 12-months, an diet effect was not significant at the 6-month assessment [32]. More research is needed to determine what frequency and regularity of Web visits needed to produce changes in dietary behaviors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Promising results are observed also for patients with NCDs. Indeed, Internet-based interventions are effective at increasing physical activity in patients with cardiovascular disease or cancer (especially the youngest patients) (18, 19). In addition to research in e-health interventions, several websites, including practical and theoretical information regarding the primary, secondary, and tertiary prevention of NCDs, have been developed in different European countries: in Sweden, in France, in Wales, in Germany, in Switzerland, and in the UK.…”
Section: Discussionmentioning
confidence: 99%
“…In some instances, the addition of web-based treatment to usual care enhances clinical outcomes (Polzien, 2006). There is evidence for both short-term and long-term behaviour change following implementation of web supports that include health behaviour reminders (Naughton et al, 2014), health education (Kanera et al, 2017), and tailored decision-making (Friederichs et al, 2015). Greatest effects are observed when these elements are combined .…”
Section: Web-based Interventionsmentioning
confidence: 99%